2008
DOI: 10.1007/s10856-008-3474-6
|View full text |Cite
|
Sign up to set email alerts
|

Silkworm and spider silk scaffolds for chondrocyte support

Abstract: Porous scaffolds can be made out of silkworm and spider silk for cartilage regeneration. Mechanical properties are related to porosity and pore size of the construct. Cell spreading and cell expression depended on the porosity and pore-size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 36 publications
0
69
0
3
Order By: Relevance
“…Rapid degradation [170] [171]; [172]; [173]; [174] Alginate Aids re-differentiation of de-differentiated chondrocytes [66] In vivo injectable options [175] Abundant and low cost Certain cross-linkage can result in poor biocompatibility [184]; [185]; [186]; [187]; [188]; [189]; [182]; [190] Dermatan sulphate, [194]; [195] …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Rapid degradation [170] [171]; [172]; [173]; [174] Alginate Aids re-differentiation of de-differentiated chondrocytes [66] In vivo injectable options [175] Abundant and low cost Certain cross-linkage can result in poor biocompatibility [184]; [185]; [186]; [187]; [188]; [189]; [182]; [190] Dermatan sulphate, [194]; [195] …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Este biopolímero extraído de gusanos de seda y arañas, se destaca por su biocompatibilidad, biodegradabilidad y excelentes propiedades mecánicas (Altman et al, 2003). Condrocitos aislados de cartílago articular humano y sembrados en soportes hechos con seda fueron capaces de adherirse, proliferar y secretar componentes de matriz extracelular del cartílago (Gellynck et al, 2008); lo mismo ha sido descrito al sembrar célu-las madre mesenquimales (CMM). Los inconvenientes de emplear soportes de seda están relacionados con el hecho de que se observan diferencias en la morfología de los condrocitos, la estructura zonal del tejido obtenido y la concentración celular necesaria para obtener el tejido cartilaginoso (Wang et al, 2006).…”
Section: Productounclassified
“…Natural dragline silk fibers have also been used to culture human primary Schwann cells and demonstrate these cells can adhere and elongate (Allmeling et al, 2006). In vivo biocompatibility of native dragline silks has also been demonstrated by subcutaneous implantation in pigs , mice and rats (Gellynck et al, 2008). These studies have revealed that spider silk is well tolerated and generates little, if any, inflammatory response in the host animal.…”
Section: Other Applicationsmentioning
confidence: 99%
“…In addition to spinning silk threads for a host of applications other uses for spider silk proteins are being pursued, including drug delivery and scaffolding materials. Both dragline silk fibers and egg sacs have been studied for their biocompatibility in a few human cell culture systems (Allmeling et al, 2006;Gellynck et al, 2008). Primary chondrocytes have been shown to attach and survive for several weeks on natural dragline silk and egg sacs (Gellynck et al, 2008).…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation